Analysis of the Current Situation and Development Strategies for Brand Building in China’s Domestic Cruise Industry - Rui, Jiang (Journal of Global Economy, Business and Finance, 2025)
Driven by policy support, manufacturing breakthroughs, and consumption upgrades, China’s domestic cruise industry has entered a transitional phase. However, brand building still faces challenges such as international competition, product homogenization, and technological shortcomings. By analyzing the current industry situation, this article proposes strategies to build brand competitiveness from five dimensions: strengthening manufacturing foundations, deepening industrial chain collaboration, innovating differentiated services, enhancing policy support, and promoting international cooperation. The aim is to drive China’s cruise industry from scale expansion to value leadership, helping it become a new growth pole in the global cruise economy.